(untitled) (International Journal of Engineering and Computer Science, 2020)
The importance of syntax analysis in the development of a compiler and Programming Languages cannot be overemphasized. Without it, we cannot even program correctly or properly. This research was performed in order to practicalize the theoretical knowledge of Compiler Construction and Automata Theory, and also with the motivation to make Nigeria’s first Programming Language. The research discusses the development of Syntax Analyzers using Parser generators and also the general program structure in the DOID Language whose Lexical Analyzer was previously discussed. The project was carried out using the de-sugaring process, Yacc/Bison Parser Generator and the C Language. The results show there is faster computation at a trade off with smaller specification set, fewer syntaxes and easy declaration of variables when compared to some other derived programming languages.